A case report and literature review of a rare lymphoma with repeated fever by pain and numbness in both lower limbs - Duan, Xiaoqiong; He, Wenhua; Chen, Rong; Jing, Min; Wang, Xin (Frontiers in Medicine, 2025)
ObjectiveExplore the clinical characteristics, diagnostic and therapeutic strategies, and prognosis of patients with intravascular large B-cell lymphoma (IVLBCL).MethodsThrough retrospective analysis of the clinical data of a patient with IVLBCL successfully treated in our department, and in combination with a review of relevant literature, we explore the pathogenesis, diagnostic methods, treatment strategies, and prognostic features of this disease.ConclusionIVLBCL as a rare subtype of extranodal large B-cell lymphoma, is characterized by high malignancy, strong invasiveness, and poor prognosis. Currently, there is no consensus on the understanding of this disease, and diagnostic and treatment standards are not yet standardized. Diagnosis primarily relies on pathological and immunohistochemical examinations. In this study, the R-CHOP regimen combined with high-dose MTX and orelabrutinib was used to treat IVLBCL patients with central nervous system involvement, achieving good therapeutic effects. However, due to the limited number of cases and the lack of large-scale clinical validation, the efficacy of this treatment regimen still requires further evaluation.